Comparative analysis of assessment practices of educational psychologists in St. John's, Newfoundland, Canada, and West Essex, England : a school psychology internship report - McLean, Dale, 1968- (1995)
Thesis (M.Ed.)--Memorial University of Newfoundland. Education Bibliography: leaves 72-74. In process